Engineering artificial machines from designable DNA materials for biomedical applications - Qi, H.; Huang, G.Y.; Han, Y.L.; Zhang, X.H.; Li, Y.H.; Pingguan-Murphy, Belinda; Lu, T.J.; Xu, F.; Wang, L. (2015)
Deoxyribonucleic acid (DNA) emerges as building bricks for the fabrication of nanostructure with complete artificial architecture and geometry. The amazing ability of DNA in building two- and three-dimensional structures raises the possibility of developing smart nanomachines with versatile controllability for various applications. Here, we overviewed the recent progresses in engineering DNA machines for specific bioengineering and biomedical applications.